Benny Wenda’s Political Propaganda about the Free Papua Issue Through Twitter - Zahidi, M. Syaprin (Jurnal Ilmiah Peuradeun, 2023)
The purpose of this study was to explain the political propaganda of the free Papua issue spread by Benny Wenda via his Twitter account. This study used a qualitative approach to analyze Benny Wenda's Twitter account. The NVivo 12 Plus software was used in this study because it can process Benny Wenda's Twitter data. This research discovered Benny Wenda's Twitter propaganda of the free Papua issue divided into 11 important topics, namely "Occupation", "media", "independence", "colonial", "today", "support", "rights", "prisoners", "Political prisoners", "people" and "Papuan". The 11 topics were further broken down into several important topics related to the issue of an independent Papua. From the analysis of Benny Wenda's Twitter account, it was also found that support for the Papuan independence movement was spread in several regions, including North America, South America, Europe, Africa, Asia, and Australia. Despite this massive support, the UN has not recognized this movement, as stated by UN Secretary-General Antonio Guterres that Papua is part of Indonesian territory through uti possideti iuris, the NY Agreement of 1962, the Act of Free Choice of 1969, and UNGA resolution 2504 (XXIV) of 1969.